Health Care in Sub-Saharan Africa: An Explorative Study of Photography as a Healing Art - Debrah, Ralitsa Diana; de la Harpe, Retha; M'Rithaa, Doreen Kainyu Mugendi (Journal of Health Informatics in Africa, 2013)
Background and Purpose: Therapeutic art plays an important role in patient recovery in hospitals. Art therapy in prescribed terms captures the use of arts and words to express ones feelings. Unlike many developed parts of the world, art rarely plays a significant role in the healing processes at hospitals in sub-Saharan Africa. While waiting to see medical officers or during admissions in the hospital, patients often find themselves either staring at blank walls or looking at health informational images — two extremes of the imagery spectrum. This may psychologically have a positive or negative impact on the health of the patient.However, research shows the importance of art in the healing process as well as in comfort and the perceived level of care. Research conducted on patients who have undergone surgery indicates that patients who had photographs mounted in their wards recovered faster than their counterparts. Similarly, researchers have also found that digital storytelling is one of the viable ways to facilitate self-healing. With the availability of Information and Communication Technologies (ICTs), there is a possibility of improving healing, facilitated within this form of cognitive-behavioural and psychodynamic process of therapy.This on-going case study, explores the use of digital photography in facilitating healing process in a hospital. It explores the use of ICT-enabled therapeutic art installation in the medical wards to aid in clinical care and practice.Methods: A qualitative approach is employed to gain deeper insight and understanding of ICTs in therapeutic art. The study focuses on maternal and child healthcare (MCH). The research is being conducted in a private-general hospital in Ghana where most of the patients are middle-income earners. Through participatory processes, images created from the input of patients and health workers were installed in the female wards and waiting areas. Interviews and observations were used to obtain impressions from patients and hospital staff about the installation in the clinic. Twenty key informants comprising doctors, nurses and patients conveyed their views.Results: Preliminary results show that, patients prefer hospital environments with therapeutic art. It relieves them of boredom and makes them feel more comfortable and relaxed. Subsequently, artistic intervention takes their mind of their ailment. It may be realised that the use of ICT- enabled therapeutic art installation has potential in facilitating healing.Conclusions: The preliminary results suggest that through simple photos created from ICTs, patients and health workers mood could be improved in the hospital. This form of phototherapy also makes patient’s appreciate art. Further research could be conducted in other private and public hospitals in cities and rural areas in other sub-Saharan African countries to validate the study.Keywords: healing; ICT; maternal healthcare; photography; sub-Saharan Africa; therapeutic art